Primitive gastrointestinal non-Hodgkin lymphomas: Retrospective clinical pathological study from 1987 to 1989 - Pastro, Dante; Czarnevicz, Daniel; Parodi, Hernán; Chiossoni, Martha (Cirugía del Uruguay, 1991)
A retrospective study of the cases of non-Hodgkin's gastrointestinal primitive lymphomas treated at Hospital Maciel between 1987 and 1989 was carried out. In order to determina cellular origin, the analysis of clinical presentation, evolutive features and immune-histochemistry was made. The following features are pointed out: male prevalence with no age preference, clinical presentation through a severe complication always, and important evolutive mortality in spite of treatment.